P04.13 LRIG3 and Soluble LRIG3 Ectodomain both inhibit the Proliferation and Invasion of Glioma cells in vitro and in vivo through modulation of Met-PI3K-Akt pathway. (19th September 2018) - Cheng, F; Mao, F; Xiao, Q; Wang, B; Guo, D
Abstract: Background: The human leucine-rich repeats and immunoglobulin-like domains (LRIG) gene family is a evolutionary conserved family comprising of LRIG1, 2, and 3, and encodes integral membrane proteins with an ectodomain, a transmembrane domain and a cytoplasmic tail. It is well documented that LRIG1 functions as a tumor suppressor in various types of cancer and LRIG2 may serve as a tumor promoter in glioma; however, although LRIG3 is low-expressed in many kinds of cancer, the function of it remains controversial. Moreover, the soluble ectodomains of LRIG1 and LRIG2 are demonstrated to be shed naturally and play similar roles to their corresponding full length proteins. Here we investigate whether the soluble ectodomain of LRIG3 (sLRIG3) is capable of being released from glioma cells and whether it has the similar founction as full-length LRIG3. Material and Methods: Cells over-expressing LRIG3 were used to determine the existence of sLRIG3 in the conditional media. Full-length LRIG3 gene and the ectodomain LRIG3 gene were transduced into GL15 and U87 cells respectively, and LRIG3 siRNA was transduced into A172 cell. The proliferation rate, cell-circle assay, migration and invasion assay were all done to detect the founction of LRIG3 and sLRIG3. Soft-agar assay and subcutaneous tumor xenograft model in nude mice were carried out to determine the influence on tumorogenesis. Western blots were used to assertain the mechanism of these phenomena.The association of LRIG3 protein level and prognosis was performed using immunohistochemical(IHC) stain of paraffin sections of glioma tissues and survival analysis of 65 glioma patients. Also, the existence of sLRIG3 were detected through westernblot in patients' body fluids. Results: First, we found that low-expressed LRIG3 protein can be easily discovered in all glioblastoma cell lines.Then, we found sLRIG3 could be detected in the conditional media of the cells over-expressing LRIG3. Further research discovered that sLRIG3 has the same function as full-length LRIG3 on inhibiting cell proliferation, invasion and tumor progression, as well as in nude mouse subcutaneous tumor xenograft model. Mechanism research indicated that sLRIG3 inhibit Met-PI3K-Akt signaling pathway as full-length LRIG3. Moreover, the IHC stain of LRIG3 and survival analysis suggested LRIG3 to be an important clinical marker of prognosis in gliomas. We further confirmed the existence of sLRIG3 through western blot in patients' plasma and tumor cystic liquids, but more precise method for quantitative detection is needed to confirm the relationship between sLRIG3 protein level and disease status. Conclusion: Our work reveals the existence of sLRIG3, which has the same tumor-supressing founctions as full-length LRIG3, and demonstrats that LRIG3 might represent as a promising new-diagnostic marker for gliomas and can be used as therapeutic agent.